Peningkatan Kemampuan Membaca Cepat melalui Penerapan Metode Gerak Mata Siswa Kelas Xii IPA A SMA Karuna Dipa Palu - Sinin, Yarni (Bahasantodea, 2024)
This study aims to 1) describe the application of eye movement methods to improve students ’ability to read quickly class XII A Science Major Students of SMA Karuna Dipa Palu, 2) describe the results of conversation eye movement methods to improve students’ ability in read quickly Class XII A Science Major Students of SMA Karuna Dipa Palu. This research was classroom action research with the subject of this research were students Class XII A Science Major Students of SMA Karuna Dipa Palu. This research conducted in two cycles, the results show, that 1) the application of the method of eye movements on student learning reading quickly Class XII A Science Major Students of Karuna Dipa Palu. Based on the student activity observation in cycle 1 was (66.15%) and teacher observation activities ( 66.67%) in cycle II has been increased, the observation of student activities was (87.69%) while the observation of teacher was very satisfying activity (91.66%). 2) the results of the application of eye movement methods in study reading quickly class XII A Science Major Student of SMA Karuna Dipa Palu, could be seen in the results of the test reading quickly cycle 1 average of speed reading and understanding the contents were 332 wpm of 76.60. In cycle 2 students’ reading speed increased 341 wpm and the students understanding about the contents in average percentage was 90.40, 82.60%. Thus, this classroom action research shows, that the application of eye movement methods can improve students’ ability to read quickly.